PENGUATAN KOMPETENSI DIGITAL MARKETING MELALUI PEMANFAATAN MARKETPLACE PADA SISWA SMK PENGUJI KOTA SUKABUMI - Prakoso, Sugih; Zaky, Muhammad; Setiadi, Sandi (PT. ABIG RIZKY PUBLISHER, 2025)
The rapid development of digital technology requires the enhancement of human resource competencies, particularly in the field of digital marketing. Vocational high school (SMK) students, as prospective workers and young entrepreneurs, need to be equipped with digital marketing skills that are relevant to the demands of the business and industrial sectors. However, students’ understanding and skills in utilizing marketplaces as a medium for developing online businesses remain limited. This community service activity aims to strengthen digital marketing competencies through the utilization of marketplaces among students of SMK Penguji, Sukabumi City. The implementation method consisted of preparation, training, mentoring, and evaluation stages using a participatory and practical approach. The results showed an improvement in students’ knowledge and skills in managing marketplace accounts, creating promotional content, and applying basic digital marketing strategies. In addition, the activity increased students’ motivation, self-confidence, and entrepreneurial spirit. Therefore, this program is considered effective in enhancing vocational students’ readiness to enter the workforce and develop independent online businesses.